2011
DOI: 10.1007/s12369-010-0088-1
|View full text |Cite
|
Sign up to set email alerts
|

When Artificial Social Agents Try to Persuade People: The Role of Social Agency on the Occurrence of Psychological Reactance

Abstract: In the near future, robotic agents might employ persuasion to influence people's behavior or attitudes, just as human agents do in many situations. People can comply with these requests, but, people can also experience psychological reactance, which may lead to the complete opposite of the proposed behavior. In this study we are interested in the social nature of psychological reactance. Social agency theory proposes that more social cues lead to a more social interaction. We argue that this also holds for psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 22 publications
3
60
0
3
Order By: Relevance
“…research (Roubroeks et al, 2011;Roubroeks et al, 2009). Contrary to our expectations, an agent with medium social agency, (i.e., with minimal social cues) provoked the lowest psychological reactance in both psychological involvement conditions (refer to Fig.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…research (Roubroeks et al, 2011;Roubroeks et al, 2009). Contrary to our expectations, an agent with medium social agency, (i.e., with minimal social cues) provoked the lowest psychological reactance in both psychological involvement conditions (refer to Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Then the negative cognitions were counted according to the procedure proposed by Dillard and Shen (2005). After that, the negative cognitions score was submitted as one of the components in psychological reactance measure in percentage form (Roubroeks, Midden, & Ham, 2011).…”
Section: Psychological Reactancementioning
confidence: 99%
See 1 more Smart Citation
“…Presenting triggers at the wrong moment in time, might not lead to compliance, or lower levels of compliance. Recent research suggested that using the wrong persuasive strategies might even lead to reactance effects causing users to become angry towards the persuasive technology, and even show behavior that opposes the target behavior [11].…”
Section: Discussionmentioning
confidence: 99%
“…Reactance has been identified as an issue in BCITs using artificial social agents [33], but the boundaries of its effects on mobile BCITs is unclear. In a worst-case scenario, a user might uninstall or game the system in response to a BCIT telling them how to act.…”
Section: Issues With Conscious Interventionsmentioning
confidence: 99%